Pengembangan LKPD Berbasis Pendidikan Karakter Dan Nilai – Nilai Islami Pada Materi SPLDV Kelas VIII - Pratiwi, Yola Novia; Ah, Nurul Imamah; Rhomdani, Rohmad Wahid; Agustina, Lady (Department of Mathematics Education , University of Jember, 2024)
The aim of this research is to produce a product in the form of LKPD based on character education and Islamic values ​​which will help students more easily understand the content of the material. The method used in this research is the Research and Development (R&D) development method with the 4D development model. The results of this research are reviewed from the validity and practicality of the product. Product validity is obtained from the average score given by 3 validators on the validation questionnaire of 83.38 and is included in the interval > 80 and is categorized as very valid. Meanwhile, product practicality was obtained from the average score given by respondents through a small-scale trial stage with a total of 6 respondents who obtained a score of 66.2 and fell into the interval 60 - 79 and were categorized as practical. Meanwhile, a large-scale trial with 31 respondents obtained a score of 81 and was included in the interval > 80 and was categorized as very practical. Based on this, it can be concluded that the product that has been developed by researchers in the form of LKPD is very valid, very practical, and in accordance with students' needs